Neck Pain and Disability: Eye Drop Installation Technique As A Causative Factor - Erkam KÖMÜRCÜ,; Selçuk KARA,; Umut Hatay GÖLGE,; Burak KAYMAZ,; Sedat ARIKAN,; Baran GENCER,; Ferdi GÖKSEL,; Ferhat GÖKMEN3, (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate a possible relationship between long standing eye drop usage and neck pain and to determine the optimal neck position while instilling the eye drop. Patients and methods: Sixty-seven patients who were between 18 to 80 years of age and admitted to the ophthalmology outpatient clinic using eye drops with the diagnosis of glaucoma for at least one year were included in the study as group 1 (n=31). A control group (group 2, n=36) was selected from age-matched individuals who did not use eye drops. The neck disability index (NDI) form and a study form which included demographic data and the method of eye drop usage of patients were filled. Results: The mean age of the patients were 55.7±11.5 and 53.5±17.1 years for group 1 and group 2, respectively. There was no significant difference in the age and sex between the groups (p=0.526 and p=0.396, respectively). Compared to the controls, the chronic eye drop usage and its application method produced significant difference in NDI (p<0.001). Also, there was a positive correlation between NDI and number of eye drop usage per a day and period of eye drop usage (p=0.003 and p=0.004, respectively). Conclusion: Neck posture which is not placed in hyperextension position during administration of eye drop may reduce postural neck malpositionrelated neck disability. Patients who are on eye drop for a long time should be informed about postural disorders and instructed to correct the administration of eye drop technique to avoid neck pain.